Inhibition of Antiviral Innate Immunity by Foot-and-Mouth Disease Virus L(pro) through Interaction with the N-Terminal Domain of Swine RNase L - Sui, Chao (J Virol, 2021)
Foot-and-mouth disease virus (FMDV) is the pathogen of foot-and-mouth disease (FMD), which is a highly contagious disease in cloven-hoofed animals. To survive in the host, FMDV has evolved multiple strategies to antagonize host innate immune responses. In this study, we showed that the leader protease (L(pro)) of FMDV, a papain-like proteinase, promoted viral replication by evading the antiviral interferon response through counteracting the 2′,5′-oligoadenylate synthetase (OAS)/RNase L system. Specifically, we observed that the titers of L(pro) deletion virus were significantly lower than those of wild-type FMDV (FMDV-WT) in cultured cells. Our mechanistic studies demonstrated that L(pro) interfered with the OAS/RNase L pathway by interacting with the N-terminal domain of swine RNase L (sRNase L). Remarkably, L(pro) of FMDV exhibited species-specific binding to RNase L in that the interaction was observed only in swine cells, not human, monkey, or canine cells. Lastly, we presented evidence that by interacting with sRNase L, FMDV L(pro) inhibited cellular apoptosis. Taken together, these results demonstrate a novel mechanism that L(pro) utilizes to escape the OAS/RNase L-mediated antiviral defense pathway. IMPORTANCE FMDV is a picornavirus that causes a significant disease in agricultural animals. FMDV has developed diverse strategies to escape the host interferon response. Here, we show that L(pro) of FMDV antagonizes the OAS/RNase L pathway, an important interferon effector pathway, by interacting with the N-terminal domain of sRNase L. Interestingly, such a virus-host interaction is species-specific because the interaction is detected only in swine cells, not in human, monkey, or canine cells. Furthermore, L(pro) inhibits apoptosis through interacting with sRNase L. This study demonstrates a novel mechanism by which FMDV has evolved to inhibit host innate immune responses.